2D-gel spot detection and segmentation based on modified image-aware grow-cut and regional intensity information. Issue 1 (October 2015) - Kostopoulou, E.; Katsigiannis, S.; Maroulis, D.
Highlights A novel approach for 2D-gel image spot detection and segmentation. The segmentation process includes a grow-cut approach with a custom update rule that takes into consideration the inherent characteristics of 2D-gel images. Real and synthetic 2D-gel images containing a total of more than 20, 000 protein spots are used for qualitative and quantitative evaluation. Better detection and segmentation performance than state-of-the-art methods.